PERAN PEMERINTAHAN DESA DALAM PELESTARIAN ADAT ISTIADAT DI DESA TANJUNG PAUH KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI TAHUN 2010-2015 - Pera Pernanda; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Customs and traditions is a reflection of the culture, religion and local customs that are aligned with the needs of the people who use them. Along with the times, the role of customs in everyday life fade, whereas customs is a concept of social life which for generations has been proven to maintain harmony in social life. As is the management of the government is a typical process consists of the actions of planning, organizing, mobilizing and controlling performed to determine and achieve the goals that have been determined through the use of human resources and other sources. This study aims to determine the role and constraints Village Government in Preservation of Customs at Tanjung Pauh Subdistrict Regency Singingi Hilir Kuantan Singingi Year 2010-2015.This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. Role of Government Tanjung Pauh so far only limited empowerment and development in order to maintain the sustainability of the customs value. The village government has not been able to design a government management in the preservation of customs. Conservation policy customs incentives only limited relief, aid procurement Indigenous Tambo book. Efforts are being made only gives moral support and encouragement to the existing indigenous stakeholders, while the more traditional institutional structures set of 4 tribes and every tribe functioning customs general overhauls.Keywords: Strategy, Government Management, Wildlife Customs